Delayed facial nerve decompression for severe refractory cases of Bell’s palsy: a 25-year experience - Ilyes Berania; Mohamed Awad; Issam Saliba; Jean-Jacques Dufour; Marc-Elie Nader (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background This study aims to assess the effectiveness of delayed facial nerve decompression for Bell’s palsy (BP). Methods We performed a retrospective case review of all patients having undergone facial nerve decompression for severe refractory BP between 1984 and 2009 at our tertiary referral center. Demographics, timing between onset of symptoms and surgical decompression, degree of facial nerve dysfunction pre- and post-operatively, follow-up length after surgery and postoperative complications were recorded. Facial nerve dysfunction was assessed using the House-Brackmann (HB) scale. Electroneuronography, electromyography and imaging results were assessed when available. Results Eighteen patients had surgery between 21 and 60 days after onset of BP (group I), and 18 patients had surgery more than 60 days after onset of symptoms (group II). In group II, 11 patients had surgery between 61 and 89 days and 7 patients after 90 days. Groups I and II showed similar functional gain and rates of improvement to HB 3 or better (11/18 vs. 11/18, p > 0.05). In group II, patients operated 60 to 89 days after onset of BP showed a significantly higher rate of improvement to HB 3 or better (9/11 vs. 2/6, p = 0.049) with higher functional gain compared to those operated after 90 days (p = 0.0293). Conclusions When indicated, facial nerve decompression for BP is usually recommended within the first 2 weeks of onset of facial paralysis. Nonetheless, our results suggest that patients with severe BP could benefit from decompression surgery within 90 days after onset of symptoms in the absence of an opportunity to proceed earlier to surgery. Further investigation is still required to confirm our findings. Trial registration Retrospective registered. IRB# 2016–6154, CE 15.154 – CA